PENGEMBANGAN E-MODUL EMBLEM BERBASIS PENDEKATAN REALISTIC MATHEMATICS EDUCATION PADA MATERI PECAHAN UNTUK ANAK KELAS V SEKOLAH DASAR - Anisa, Hanifatul; Sumaji, Sumaji; Riswari, Lovika Ardana (STKIP Persada Khatulistiwa Sintang, 2024)
The background of this research is the limited learning resources used by students in learning. The efforts made to overcome this problem through developing learning resources in the form of e-module emblems based on the Realistic Mathematic Education (RME) approach. This research aims to determine the feasibility and response of students on the emblem e-module based on the RME approach of fraction material at class V elementary schools. The research method used is Research and Development according to Borg and Gall which has been modified into 7 stages. This research was conducted at SD Negeri 3 Adiwarno. The research subjects involved in this research were fifth grade elementary school teachers and students, media experts and material experts. The research instruments used were interviews, documentation and e-module quality questionnaires to see the feasibility of the e-module being developed. Based on the results of the validation test analysis, an average of 92.78% was obtained, consisting of a media expert assessment of 93.23% and a material expert assessment of 92.34%. Also supported by the calculation of the student response questionnaire after using the e-module was 90.47% achieved the very good category. Thus, it can be concluded that the RME-based emblem e-module development product is very feasible and very good to be used as a learning resource in assisting the learning activities of Mathematics fractions for fifth grade elementary school students.